Magazine “Okhotnichy Vestnik”: History of its Origin and Functioning in Specialized Printing Market - A. V. Lyapina (Научный диалог, 2021)
The history of one of the most popular Moscow magazines of nature and hunting “Okhotnichy Vestnik” (1901—1918), which for eighteen years has been associated with the trading company of the same name, is considered. The archival materials from the funds of the Russian State Historical Archive, the Central State Archive of Moscow, related to the publication and trading partnership “Okhotnichy Vestnik” are analyzed. On the basis of the historical-typological method, the program, content features of the magazin, ways of interacting with readers and competitors are studied, the reasons for its popularity during the period of historical catastrophes are considered. The novelty of the research is determined both by the empirical material itself — archival files not previously introduced into scientific circulation, and by the subject — the history of the emergence and functioning of the magazine “Okhotnichy Vestnik”. It is concluded that in the conditions of socio-political unrest and fierce competition for the reader, during the crisis of hunting journalism, “Okhotnichy Vestnik” retained the status of a fairly authoritative and influential publication thanks to the flexible policy of editors-publishers and effective methods of activity of the trade and industrial partnership “Okhotnichy Vestnik”. The history of the “Okhotnichy Vestnik” makes it possible to present a more complete picture of the formation of a new type of specialized printing.